Heteropore covalent organic frameworks: a new class of porous organic polymers with well-ordered hierarchical porosities. Issue 22 (27th September 2018) - Liang, Rong-Ran; Zhao, Xin
Abstract : This review highlights the development of heteropore covalent organic frameworks, a new class of porous organic polymers which exhibit well-ordered heterogeneous/hierarchical porosities. Abstract : Covalent organic frameworks (COFs), a class of crystalline porous organic polymers with designable and predictable structures which can be constructed by atomically precise integration of organic units via covalent bonds, have drawn considerable attention over the past decade due to their versatile applications in many fields. Very recently, we have devised a new class of COFs coined as heteropore COFs by introducing different kinds of pores into one COF structure. In contrast to the traditional COFs which only hold uniform pores and thus display homogeneous porosity, heteropore COFs exhibit heterogeneous/hierarchical porosities. In this review, the state of the art development of heteropore COFs is summarized and personal perspectives on this new generation of porous organic materials are also discussed.